تطبيق كتاب نمط العبارات في القرآن لترقية حفظ القرآن - M. Fathor Rohman; Muhammad Iqbal Trenggono; Abdurrahman AL Sayid Abdul Ghafar (KILMATUNA: Journal of Arabic Education, 2021)
Many educational institutions in Indonesia are based on Islamic boarding schools, teaching their students not only proficient in Arabic but also able to memorize the Koran well. Including the Madrasah Aliyah Ma'arif 7 Lamongan educational institution is an institution that combines the state curriculum and pesantren by including Quran memorization material, it's just that students' memorization activities are not so optimal, with achievements below the KKM Madrasah value, among the inhibiting factors is the lack of time and materials. minimal teaching which causes students not to have the enthusiasm to memorize. So that in improving memorization, the author tries to use the Qur'an expression pattern book to improve student memorization, especially students of class XI Madrasah Aliyah Ma'arif 7 Lamongan. This research is a Classroom Action Research with Kurt Lewin's model which in one cycle consists of four steps, planning, implementation, observation and reflection. While the data collection techniques used interviews, observations, questionnaires and tests. The results of this study in the application of the Al-Qur'an Expression Pattern Book an increase in student activity in each cycle, and this can be proven by the average value of students in the first cycle of 79, an increase in the second cycle of 80.5 with the percentage learning outcomes by 76% and in the second cycle increased by 90%, therefore the research was declared successful because it achieved performance indicators.